1998
DOI: 10.1080/00016489850154766
|View full text |Cite
|
Sign up to set email alerts
|

Children with Nocturnal Upper Airway Obstruction: Postoperative Orthodontic and Respiratory Improvement

Abstract: Oximetry and airflow recordings may be normal in children who benefit from treatment of anamnestic nocturnal obstruction. Craniofacial deformities are common and improve significantly with surgical treatment of the airway obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It has been reported that breathing disorders can cause maxillofacial growth problems, vertical facial development, and a skeletal class II malocclusion, and that they can lead to a posterior crossbite 17. In a recent study by Kim et al, children with skeletal class II malocclusions and retrusive mandibles had smaller pharyngeal airway dimensions than children with skeletal class I malocclusions 18…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that breathing disorders can cause maxillofacial growth problems, vertical facial development, and a skeletal class II malocclusion, and that they can lead to a posterior crossbite 17. In a recent study by Kim et al, children with skeletal class II malocclusions and retrusive mandibles had smaller pharyngeal airway dimensions than children with skeletal class I malocclusions 18…”
Section: Introductionmentioning
confidence: 99%
“…With abnormal breathing, a growing child may show problems with maxillofacial growth, such as a vertical facial pattern, skeletal Class II malocclusion, and posterior crossbite 9. However, the jaw bones have been verified to grow normally once the respiratory functions are recovered by removing the factors that infringe breathing 10…”
Section: Introductionmentioning
confidence: 99%
“…In total, the authors identified 21 trials but only 20 are found in a table that lists the studies with a score of 13.2 to 2.3) (A: 0; B: 14; C: 6; D: 0) [99], [100], [108], [164], [165], [166], [167], [168], [178], [183], [184], [185], [186], [187], [188], [189], [190], [191], [192], [193]. Further calculations (CI, significance level) are not provided.…”
Section: Resultsmentioning
confidence: 99%